Entrepreneurship in Culinary Arts: The Costa Rica experience with university students - Juan Antonio Aguirre G; Beatriz Avendaño (PASOS Revista de Turismo y Patrimonio Cultural, 2011)
The tourism industry of Costa Rica represents 7.5% of GNP, 21% of total exports earning and of that contribution the food and beverages subsector represents 28%. The purpose of this re- search was to indentify, potential elements and obstacles in young university culinary arts students in Costa Rica, largest culinary arts students. The study was conducted among culinary arts students at the Universidad Interamericana de Costa  Rica, the interviews conducted were 237 the entire en- rollment of the culinary arts school. The findings indicate that .Absence of tradition, culture among the young students and need of family and peers supports appear to be relevant and a source of need by the group. Lack of general business and entrepreneurship training is recognize by both groups a weakness and as a need. Coaching and support for women entrepreneurs is very relevant in both the administrative and technical aspects of the young students of culinary arts The consideration of this information is important if we are to create with culinary arts training , the new breed of professional chefs entrepreneurs needs for the industry expansion in the years to come in Costa Rica and the region